Oportunidades para implementação de práticas de Economia Circular na gestão de materiais de consumo em uma instituição federal de ensino superior - Silva, Elieth Shirley dos Santos (Universidade Federal de São Carlos)
The concept of the Circular Economy has increasingly gained prominence as an effective economic model that combines savings and profit. It represents a viable alternative for sustainable development compared to the current Linear Economy model (extract, produce, discard), given that the scarcity of resources/raw materials, combined with population growth, demands a new form of production and consumption. Therefore, although this transition is still slow, organizations and companies around the world have adopted holistic systems with the aim of retaining valuable resources, regenerating, and maintaining living systems. In this sense, universities also play a crucial role in this transition, not only as producers of knowledge but also as agents that implement the fundamentals of the Circular Economy in internal processes and services. They can contribute positively with examples of solutions to address global challenges, promoting sustainability through feedback from consumption, eliminating waste and pollution, keeping products and materials in use longer, and regenerating natural systems. Thus, this study aims to identify opportunities for implementing Circular Economy practices in the processes and services performed in the management of consumables by the Federal University of Mato Grosso Foundation (UFMT). To this end, two Systematic Literature Reviews and a case study were conducted, applying the principles of the ReSOLVE framework to each stage of the process studied to identify opportunities for implementing the Circular Economy. It was identified that the institution has already implemented several practices related to the strategic objectives of the ReSOLVE framework in the process studied, as well as the possibility of implementing new actions. Therefore, it is expected that the identified and proposed practices can contribute positively to increasing the circularity of consumables at the institution studied and at similar institutions, as well as to improving process efficiency, reducing environmental impact and contributing to more sustainable development.
Opportunities for implementing Circular Economy practices in the management of consumable materials at a Ffderal higher education institution
Keywords: Economia Circular; Instituição de ensino superior; Materiais de consumo; ReSOLVE; Circular Economy; Higher education institution; Consumer materials; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; 11. Cidades e Comunidades Sustentáveis; 12. Consumo e Produção Responsáveis; 13. Ação contra a Mudança Global do Clima